Comparing Apples With Apples: Women Faculty Research Productivity in Vietnamese Higher Education - Chunhai Gao; Sabika Khalid; NGUYEN Van Thang; Endale Tadesse (SAGE Open, 2023)
For decades, abundant studies have illustrated the vast scholarly publication disparity between male and women academics. Exhaustingly, in 21st-century higher education, women’s academic research participation is below the world average, except in a few countries that comprehensively studied their faculties and personal and institutional agencies to restore parity. Higher education is widely discussed in Vietnam as incompetent academics with a shred of scholarly publications and venerable gender disparities. Hence, the current study sought to contribute robust policy and practical implications for stakeholders by inspecting women’s faculties solely to shed light on the root hindrances of their scholarly share. Remarkably, the findings of the study demonstrate that women faculty members have promising scholarly contributions in disciplines where women scientists are marginalized, that having children becomes a notable motivator for mothers in academia, and that there is genuine support from a husband who understands the worth of his wife’s research contribution to the institution and family.